Development of a surface plasmon resonance biosensor for accurate and sensitive quantitation of small molecules in blood samples - Minyu Qi; Diya Lv; Ying Zhang; Dongyao Wang; Xiaofei Chen; Zhenyu Zhu; Zhanying Hong; Yifeng Chai; Hai Zhang; Yan Cao (Elsevier, 2022)
Therapeutic drug monitoring (TDM) has played an important role in clinical medicine for precise dosing. Currently, chromatographic technology and immunoassay detection are widely used in TDM and have met most of the needs of clinical drug therapy. However, some problems still exist in practical applications, such as complicated operation and the influence of endogenous substances. Surface plasmon resonance (SPR) has been applied to detect the concentrations of small molecules, including pesticide residues in crops and antibiotics in milk, which indicates its potential for in vivo drug detection. In this study, a new SPR-based biosensor for detecting chloramphenicol (CAP) in blood samples was developed and validated using methodological verification, including precision, accuracy, matrix effect, and extraction recovery rate, and compared with the classic ultra-performance liquid chromatography-ultraviolet (UPLC-UV) method. The detection range of SPR was 0.1-50 ng/mL and the limit of detection was 0.099 ± 0.023 ng/mL, which was lower than that of UPLC-UV. The intra-day and inter-day accuracies of SPR were 98%-114% and 110%-122%, which met the analysis requirement. The results show that the SPR biosensor is identical to UPLC-UV in the detection of CAP in rat blood samples; moreover, the SPR biosensor has better sensitivity. Therefore, the present study shows that SPR technology can be used for the detection of small molecules in the blood samples and has the potential to become a method for therapeutic drug monitoring.